Microwave processing of vermiculite - Folorunso, Olaosebikan (2015)
Vermiculite is a clay mineral that is generally used for a wide range of applications such as in agricultural, horticultural and construction industries. This is due to its various properties which include high porosity, lightweight, thermo-insulating, non-toxic and good absorption capacity when exfoliated. The objective of this research was to critically evaluate the fundamental interaction of electromagnetic waves with vermiculite from different source locations and to understand the mechanism of exfoliation in an applied microwave field. When vermiculite minerals are placed under the influence of high electric fields, they expand due to the rapid heating of their interlayer water, which subsequently builds up pressure that pushes apart the silicate structure. The degree of exfoliation is directly related to the intensity of the applied electric field. The principal areas covered in this thesis include: a detailed review of the fundamentals of microwave processing and issues surrounding scale up; a critical literature review of vermiculite mineralogy, and previous methods of vermiculite processing and their limitations; understanding the interaction of microwave energy with vermiculite by carrying out mineralogical and dielectric characterisation; microwave exfoliation tests of vermiculite minerals from different source locations and a comparative energy and life cycle analysis of microwave and conventional exfoliation of vermiculite.